Gender Equality: Deprivation of Women’s Rights in the Pitti Rambang Tradition - Ghello, Eltria Natasya; Ramadhan, Ahmad Jayhan; Nahuddin, Yusuf Eko; Indrayanti, Kadek Wiwik; Budiono, Indro; Ghufron Az, Muhammad (Jurnal Cakrawala Hukum, 2024)
Gender equality is an essential issue in the context of human rights. In traditional Indonesian society, practices such as Pitti Rambang or Kawin Tangkap still take place and often contradict the principles of gender equity. This study uses a normative method to evaluate the effectiveness of applicable laws in protecting women. It analyzes the gap between ideal legal norms (das sollen) and social reality (das sein), such as national and international legal perspectives, and how customs can create gender inequality. The study highlights the importance of legal reforms that refer to the Law on the Elimination of Domestic Violence and the International Convention on the Elimination of Discrimination against Women (CEDAW). The results show the need for collaboration between law enforcement and cultural approaches to create inclusive and equitable solutions for women in Indigenous communities